-3x-17=-9x+19

Simple and best practice solution for -3x-17=-9x+19 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -3x-17=-9x+19 equation:


Simplifying
-3x + -17 = -9x + 19

Reorder the terms:
-17 + -3x = -9x + 19

Reorder the terms:
-17 + -3x = 19 + -9x

Solving
-17 + -3x = 19 + -9x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '9x' to each side of the equation.
-17 + -3x + 9x = 19 + -9x + 9x

Combine like terms: -3x + 9x = 6x
-17 + 6x = 19 + -9x + 9x

Combine like terms: -9x + 9x = 0
-17 + 6x = 19 + 0
-17 + 6x = 19

Add '17' to each side of the equation.
-17 + 17 + 6x = 19 + 17

Combine like terms: -17 + 17 = 0
0 + 6x = 19 + 17
6x = 19 + 17

Combine like terms: 19 + 17 = 36
6x = 36

Divide each side by '6'.
x = 6

Simplifying
x = 6

See similar equations:

| 6+7q=8+6q | | 1-4a=22 | | r/15=45 | | -(x-7+2y)= | | w-14=3.4 | | 7(3x+2)=8(x+5)-17 | | (3a+7)(2a+5)= | | -5x+4=-31 | | 30(13.10)=17x+2 | | -3(6r-5+9s)= | | 44(x+10)-6=-3(x-2) | | 9008c-28c/70=97+78c | | a+2b=5c | | 2[x-2(3-x)-3x]=4(5-x) | | 10n-4=46 | | -0.83w-0.5=1.67w-2.5 | | 0.17-0.03(x+2)=-0.02(2-x) | | m/12=0 | | 8(5x+4y+3)= | | .50t=-8 | | x+2x=63 | | 4x-6x-11=-2x+6-11 | | -1+6(-n+5)=-7(-n-4)+2 | | 6(x-4)=3x | | 2y^2=7y-3 | | 7(8n-1)+8=8(7n+8) | | -5w-15=-w+1 | | -5x-15=-1w+1 | | n/8=24 | | 5x+32=14x-49 | | 0.16(y-7)+0.20y=0.04y-0.05(40) | | -5x-15=-w+1 |

Equations solver categories